Design and Analysis of Composite Propeller Blade for Aircraft (International Journal of Innovative Research in Computer Science & Technology, 2022)
The work in this paper primarily focuses on  the modelling and analysis of a plane's propeller blade for  strength. The geometry of a propeller blade is a sophisticated  3D model. CATIA V5 R20 is utilised to generate the blade  model, which necessitates the usage of high-end modelling  CAD software. This document provides a brief overview of  Fiber Reinforced Plastic materials as well as the benefits of  employing composite propellers over traditional metallic  propeller blades. The purpose of this research is to use finite  element analysis to analyse the metal and composite strength  of the propeller blade. We conducted static and modal  analysis for isotropic materials using ANSYS software, as  well as linear layer analysis for orthotropic materials. FEA  methods were used to investigate two distinct types of  propellers, namely aluminium, E-glass, and carbon fibre.
Keywords: Propeller CATIA; Isotropic